The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/molecules27144400
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Benefits and Problems of Curcumin with Respect to Human Health

Abstract: Curcumin is the most important active component in turmeric extracts. Curcumin, a natural monomer from plants has received a considerable attention as a dietary supplement, exhibiting evident activity in a wide range of human pathological conditions. In general, curcumin is beneficial to human health, demonstrating pharmacological activities of anti-inflammation and antioxidation, as well as antitumor and immune regulation activities. Curcumin also presents therapeutic potential in neurodegenerative, cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 124 publications
0
26
0
Order By: Relevance
“…However, due to its low solubility and poor bioavailability, its therapeutic application is limited [ 22 ]. Cur has been discovered to have a variety of biological and anticancer activities, including antibacterial, antioxidant, and anti-inflammatory [ 23 ]. Curcumin has been studied for its ability to alleviate various cancers, including colon, and breast cancer [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its low solubility and poor bioavailability, its therapeutic application is limited [ 22 ]. Cur has been discovered to have a variety of biological and anticancer activities, including antibacterial, antioxidant, and anti-inflammatory [ 23 ]. Curcumin has been studied for its ability to alleviate various cancers, including colon, and breast cancer [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these studies, and others, showed that curcumin may be effective in controlling circulating blood glucose concentrations and has the potential to slow the progression of type 2 diabetes (15,(70)(71)(72). Turmeric is a safe food that healthy people can eat in moderation without getting sick (16).…”
Section: Health Benefits and Biological Impacts Of Curcuminmentioning
confidence: 99%
“…That is, it is used for nutrients that indicate the absorption value. A food with a high ORAC value is more antioxidants, protects against cancer, and slows aging (16).…”
Section: Health Benefits and Biological Impacts Of Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…The research and application of acrylic resin-based pharmaceutical excipients are very extensive, especially in the field of pharmacy ( Bettencourt et al, 2010 ; Villanova et al, 2011 ; Liu S. et al, 2022 ). In view of the shortcomings of many drugs directly administered, coating technology can effectively solve such problems.…”
Section: Introductionmentioning
confidence: 99%